2022
DOI: 10.3390/antiox11061056
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compound, Antioxidant, and Radical Scavenging Activity of Some Plant Aqueous Extracts for Enhancing Shelf Life of Cold-Stored Rabbit Meat

Abstract: The potential radical scavenging, antioxidant activities (DPPH and ABTS) and bioactive constituents of several plant aqueous extracts (Curcuma longa, CL; Myristica fragrans, MF; Zingiber officinale, ZO; Cymbopogon citratus, CC and Thymus vulgaris, TV as well as their mixture) were investigated. The effect of these extracts on quality aspects (sensory characteristic, color traits, and Thiobarbituric acid) of rabbit meat during a 16-day cold (4 ± 2 °C) storage were investigated. Total phenolics and flavonoid con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 31 publications
1
6
1
Order By: Relevance
“…The TPC results of the ground ginger rhizome and nutmeg extracts were in agreement with some previously published data (TPC = 101.6–2314.0 mg GA/100 g and 49.82–268.0 mg GA/100 g for ginger and nutmeg, respectively) [ 35 , 36 , 37 , 38 , 39 , 40 ]. However, these authors [ 36 , 37 , 39 ] found significantly lower radical scavenging capacities of ginger and nutmeg against DPPH radical (0.922 mmol TE/100 g and 0.844 mmol TE/100 g, respectively) and ABTS radical cations (0.348 mmol TE/100 g and 0.455–19.1 mmol TE/100 g, respectively) compared with DPPH and ABTS values for the studied extracts of the two spice powders. Discrepancies in the antioxidant properties of spices can be explained by the influences of genetic, agronomic, and environmental factors, as well as different solvents and techniques used in the preparation of spice samples, which would affect the antioxidant contents.…”
Section: Resultssupporting
confidence: 92%
“…The TPC results of the ground ginger rhizome and nutmeg extracts were in agreement with some previously published data (TPC = 101.6–2314.0 mg GA/100 g and 49.82–268.0 mg GA/100 g for ginger and nutmeg, respectively) [ 35 , 36 , 37 , 38 , 39 , 40 ]. However, these authors [ 36 , 37 , 39 ] found significantly lower radical scavenging capacities of ginger and nutmeg against DPPH radical (0.922 mmol TE/100 g and 0.844 mmol TE/100 g, respectively) and ABTS radical cations (0.348 mmol TE/100 g and 0.455–19.1 mmol TE/100 g, respectively) compared with DPPH and ABTS values for the studied extracts of the two spice powders. Discrepancies in the antioxidant properties of spices can be explained by the influences of genetic, agronomic, and environmental factors, as well as different solvents and techniques used in the preparation of spice samples, which would affect the antioxidant contents.…”
Section: Resultssupporting
confidence: 92%
“…The degree of color change corresponds with the sample's antioxidant activity (Sen Gupta & Ghosh, 2013). However, at higher concentrations, potential color interference by β-CBP may result in a lower measured DPPH activity (Miguel, 2010;Al Jumayi, 2022), as evident in the results and IC50 value (Fig. 1e and Table 1 The alkaline DMSO, used as a superoxide-generating system, reacts with NBT to yield colored diformazan .…”
Section: Discussionmentioning
confidence: 97%
“…Synthetic preservatives have been used in meat industries to prevent spoilage and improve safety. Recently, growing consumer awareness of natural bioactive compounds is palpable, as these compounds could be valid alternatives to partially replace synthetic compounds and avoid harmful side effects on human health [6]. Moreover, due to their beneficial effects on digestive function and growth, and their antimicrobial and antioxidant properties, the use of spices and herbs containing bioactive molecules, such as polyphenols, as feed supplements in animal production has been investigated in the last decade to improve rabbit health and meat quality attributes [7,8].…”
Section: Introductionmentioning
confidence: 99%